Mental Health in Doctoral Students: Individual, Academic, and Organizational Predictors - Estupiñá, Francisco J.; Santalla, Álvaro; Prieto-Vila, Maider; Sanz, Ana; Larroy, Cristina (Psicothema, 2024)
Background: The mental health of doctoral students is a matter of concern, and several variables appear to be associated with the state of their mental health. However, there have been no studies on the population of doctoral students in Spain to date using validated instruments. Method: A cross-sectional observational study was conducted to assess mental health in 1,018 doctoral students. The impact of personal, academic, psychological, and social/organisational variables on their mental health was assessed. Results: Between 50% and 60% of the sample might be experiencing a common psychological disorder, while 18.8% of the sample might be experiencing passive suicidal ideation. In addition, using binary logistic regression, significant predictors of negative mental health were identified, including: sociodemographic variables (being female); academic variables (longer time spent in a doctoral programme); psychological variables (lower life satisfaction; greater interference and less clarity about negative emotions); and social and organisational variables (greater fear of losing tuition rights, lower social support, and greater interference of academic work with personal life). Conclusions: Doctoral students need measures to remedy and prevent mental health issues based on improving self-care and emotion regulation, promoting social support at university, and reducing the pressure of losing tuition rights among final-year students.